2007
DOI: 10.1177/0040517507080691
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized and Activated Non-wovens as High-Performance Acoustic Materials: Part I Noise Absorption

Abstract: Noise absorption is one method for noise reduction in engineering. The material acoustic property for noise absorption is principally based on the efficiency of material structures for damping sound wave reflections. In this paper, three non-woven composites with activated carbon fiber (rayon precursor) non-woven as a surface layer and cotton, ramie, and polypropylene fiber non-wovens as base layers were produced. Their noise absorption coefficients were measured using the Brüel and Kjær impedance tube instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 20 publications
(21 reference statements)
0
40
0
Order By: Relevance
“…Because of this majority of the workers in these industries are disturbed from the noise in their workplaces, and few of them were suffering hearing problems 2 . The study conducted using Non-woven composites with activated carbon fiber (rayon precursor) nonwoven as a surface layer and cotton, ramie, and polypropylene fiber non-wovens as base layers concluded that the activated carbon fiber composites exhibited an exceptional ability to absorb normal incidence sound waves 3 .Acoustic characteristics of structured needle punched floor coverings in relation to fiber fineness, surface effect, punch density, areal density, and chemical bonding process has been studied. It has been found that higher levels of punch density and higher areal density caused the noise reduction coefficient (NRC) of the fabrics 4 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of this majority of the workers in these industries are disturbed from the noise in their workplaces, and few of them were suffering hearing problems 2 . The study conducted using Non-woven composites with activated carbon fiber (rayon precursor) nonwoven as a surface layer and cotton, ramie, and polypropylene fiber non-wovens as base layers concluded that the activated carbon fiber composites exhibited an exceptional ability to absorb normal incidence sound waves 3 .Acoustic characteristics of structured needle punched floor coverings in relation to fiber fineness, surface effect, punch density, areal density, and chemical bonding process has been studied. It has been found that higher levels of punch density and higher areal density caused the noise reduction coefficient (NRC) of the fabrics 4 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using activated carbon fibers on the surface of composites, Chen and Jiang [24] obtained a structure with two porous layers, a large diameter porous layer confined between the fiber and the yarn and a small diameter porous layer produced at the surface of the activated carbon fibers. Activated carbon fibers used in a nonwoven composite resulted in an increase in total volume of porous space improving sound absorption performance of the material at frequencies between 0.05-1.6 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…Kenaf, jute and cotton fibers mixed with polyester and polypropylene in combination with an automotive padding material resulted in significant improvement in sound absorption properties [23]. Rayon activated small pore sized carbon layers combined with a nonwoven layer of cotton, polypropylene and rami fiber mixture, revealed better sound absorption rates [24]. Banana, bamboo and jute fibers mixed with polypropylene, yielded improved sound absorption properties [25].…”
Section: Introductionmentioning
confidence: 99%
“…The ACF composites exhibit an exceptional ability to absorb normal incidence sound waves in comparison to composites with either glass-fiber or cotton fiber or ramie fiber, as illustrated in Fig. 4 (Chen and Jiang 2007). Considering the light weight, biodegradability, and low cost of the raw material, activated carbon products have potential to be used as high-performance and cost-effective acoustical materials.…”
Section: Composites With Other Additives And/or Polymer Matrix Systemsmentioning
confidence: 99%